ICE: No Advantage to Adding Capecitabine to Ibandronate in High-Risk Early BC - Lederman, Lynne (MD Conference Express, 2014)
Previous studies suggested that elderly patients with early moderate- to high-risk breast cancer might benefit from adjuvant combination capecitabine plus ibandronate. The phase 3 ICE study showed no difference in invasive disease-free survival or overall survival at 3 or 5 years between those receiving capecitabine plus ibandronate vs ibandronate alone.